Aquatic biota in the Peruvian Amazon: diversity and uses as environmental indicators in the lower Urubamba (Cusco - Ucayali) - Ortega, Hernán (2010)
In this paper we apply biological indices of environmental quality and conservation, based on biological monitoring conducted between 2003 and 2009 in five localities of the Bajo Urubamba River. Communities of plankton, benthos and fishes were studied. The diversity of plankton was 170 species, mainly based on Chlorophyta and Bacillariophyta. The benthos included 112 species, mainly larvae and adults of Arthropoda (Insecta). 176 fish species were recorded, represented by 26 families and six orders. The quality of the study area ranged from normal to very good, according to the index %ETP. The conservation index of aquatic environments (IBI) gave the higher values for Miari and Sepahua. The high diversity of the communities studied could be related to the heterogeneity of habitats and greater resources than are observed in the lower part of the study area.